Definition and management of varicella zoster virus-associated meningoradiculitis: a case report. (December 2016) - Luisier, Vincent; Weber, Lalensia; Fishman, Daniel; Praz, Gérard; Ghika, Joseph-André; Genoud, Didier; Chabwine, Joelle
Abstract Background The varicella zoster virus affects the central or peripheral nervous systems upon reactivation, especially when cell-mediated immunity is impaired. Among varicella zoster virus-related neurological syndromes, meningoradiculitis is an ill-defined condition for which clear management guidelines are still lacking. Zoster paresis is usually considered to be a varicella zoster virus-peripheral nervous system complication and treated with oral antiviral therapy. Yet in the literature, the few reported cases of herpes zoster with mild cerebral spinal fluid inflammation were all considered meningoradiculitis and treated using intravenous antiviral drugs, despite absence of systemic signs of meningitis. Nevertheless, these two clinical pictures are very similar. Case presentation We report the case of an alcohol-dependent elderly Caucasian man presenting with left lower limb zoster paresis and mild cerebral spinal fluid inflammation, with favorable outcome upon IV antiviral treatment. We discuss interpretation of liquor inflammation in the absence of clinical meningitis and implications for the antiviral treatment route. Conclusion From this case report we suggest that varicella zoster virus-associated meningoradiculitis should necessarily include meningitis symptoms with the peripheral neurological deficits and cerebral spinal fluid inflammation, requiring intravenous antiviral treatment. In the absence of (cell-mediated) immunosuppression, isolated zoster paresis does not necessitate spinal tap or intravenous antiviral therapy.